Pengaruh Perceived Ease of Use, Perceived Usefulness dan Perceived Risk terhadap pembayaran Cashless pada UMKM di Kota Manado - Mangambe, Diony Jasinta; Pontoh, Winston; Datu, Christian (Manajemen Bisnis dan Keuangan Korporat, 2025)
The rapid advancement of digital technology has transformed global payment systems, including in Indonesia, with the increasing adoption of cashless payments that offer greater efficiency, security, and accessibility compared to conventional methods. However, the adoption rate of this technology among Micro, Small, and Medium Enterprises (MSMEs) remains varied. This study aims to examine the influence of perceived ease of use, perceived usefulness, and perceived risk on cashless payment usage among MSMEs in Manado City. A quantitative approach was employed with a population comprising MSME actors who use cashless payments. A total of 95 respondents were selected through purposive sampling. Data were collected via questionnaires and analyzed using multiple linear regression with the JAMOVI software. The results reveal that perceived ease of use has a positive and significant effect on cashless payments, perceived usefulness has a positive but insignificant effect, and perceived risk has a negative and insignificant effect. These findings indicate that ease of use is the primary driver of cashless payment adoption among MSMEs, while perceived usefulness and perceived risk do not significantly influence adoption. This study contributes to the development of the Technology Acceptance Model (TAM) literature in the MSME context and provides practical implications for digital payment service providers to enhance cashless payment adoption.